(E)-1-[4-(Methylsulfanyl)phenyl]-2-(2,3,4-trimethoxyphenyl)ethene - Gielara-Korzańska, Agnieszka (International Union of Crystallography, 2012)
In the title compound, C(18)H(20)O(3)S, the rings are almost coplanar [inter-ring dihedral angle = 6.6 (2)°]. In the crystal, weak C—H⋯O hydrogen bonds between the methoxy groups connect adjacent molecules, giving chains which extend along [001].